Novel Thioureido Derivatives Carrying Thione and Sulfonamide Moieties Induce the Cytoprotective Enzyme NAD(P)H:Quinone Oxidoreductase 1 - M. Ghorab1, Mostafa; Higgins2, Maureen; T. Dinkova-Kostova2, Albena; S. Alsaid1, Mansour; A. Shahat1, Abdelaaty (Asian Journal of Chemistry, 2014)
Plant-derived molecules have played an important role for the prevention and treatment of cancer. On the account of the reported anticancer activity of quinazolines containing the biologically active sulfonamide moieties, a novel series of thioureido and quinazoline derivatives were synthesized using methyl 2-isothiocyanatobenzoate (2) as a strategic starting material. The present work reports the synthesis and NAD(P)H:quinone oxidoreducase 1 (NQO1) inducer activity of three novel thioureido and quinazoline derivatives 3, 4 and 5. The thioureido derivative 3 was obtained in good yield via reaction of compound 2 with sulfaphenazole in absolute ethanol at room temperature. Reaction of compound 2 with sulfaphenazole and/ or sulfadimethoxazine in absolute ethanol containing a catalytic amount of triethylamine furnished the corresponding sulfonamide derivatives 4 and 5, respectively. The structure of the newly synthesized compounds was confirmed on the basis of elemental analyses, IR, 1H NMR and 13C NMR spectra. Evaluation of the NQO1 enzyme activity in murine cells exposed to the new compounds revealed that introduction of the thioureido moiety confers inducer activity. Furthermore, incorporating the thioureido moiety within a heterocyclic ring system increases the inducer potency.